2019
DOI: 10.1039/c9dt01555h
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the scope of alkylboryl-bridged N → B-ladder boranes: new substituents and alternative substrates

Abstract: A series of new boranes capable of forming intramolecular N → B-heterocycles has been prepared and their properties have been studied by electrochemical methods and UV-vis-spectroscopy complemented by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…The photophysical and DFT experiments showed that the electronic properties of the synthesized boranes can be tuned by varying the substituents on boron. The same methodology was further extended to 104,105 prepare a series of conjugated ladder type B-N coordinated boranes (86,87) by the two-fold hydroboration reaction of quarterpyridine, pyrimidine, and 1,5-naphthyridine precursors with 9H-BBN and Piers' boranes ((C 6 H 5 ) 2 BH). Photophysical and electrochemical experiments showed that the optical band gaps of these boranes are reduced and their electron affinities are increased to between −3.4 and −4 eV, which make them suitable candidates for use as n-type organic semiconductors.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photophysical and DFT experiments showed that the electronic properties of the synthesized boranes can be tuned by varying the substituents on boron. The same methodology was further extended to 104,105 prepare a series of conjugated ladder type B-N coordinated boranes (86,87) by the two-fold hydroboration reaction of quarterpyridine, pyrimidine, and 1,5-naphthyridine precursors with 9H-BBN and Piers' boranes ((C 6 H 5 ) 2 BH). Photophysical and electrochemical experiments showed that the optical band gaps of these boranes are reduced and their electron affinities are increased to between −3.4 and −4 eV, which make them suitable candidates for use as n-type organic semiconductors.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…The emission of complexes showed a red shifted band with respect to their respective ligands. A similar methodology was also adopted to make 118 phenanthroimidazole based boron compounds (105). All the compounds showed moderate to good quantum yields in the solution state and moderate solid state quantum yields.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…[57,58] Hydroboration of suitable substrates can also yield a broad range of N!B-heterocycles. [59][60][61][62][63][64][65][66] Recently we developed strategies for the synthesis of N!Bheterocycles by building-up the N-heterocyclic component through cycloaddition-reactions. We found that both 1,3-dipolar [3 + 2] azide-alkyne cycloaddition [67,68] and cobalt-mediated [2 + 2 + 2] cycloaddition between nitriles and alkynes [69] are highly efficient tools for the preparation of electronically and structurally diverse N!B-ladder boranes.…”
Section: Introductionmentioning
confidence: 99%
“…and electrophilic C−H‐borylation [57,58] . Hydroboration of suitable substrates can also yield a broad range of N→B‐heterocycles [59–66] …”
Section: Introductionmentioning
confidence: 99%
“…13 Due to the high stability of the B-C bonds, BC 4 boranes exhibit high stereochemical stability. 14 To date, chiral tetrahedral boranes with B-N, [15][16][17][18][19][20][21][22][23][24][25][26][27] B-O, [28][29][30][31] B-H, 32,33 and boron-heteroatom [34][35][36][37] bonds have been synthesized and the stereochemistry of the compounds has been studied extensively. For example, Toyota has reported stable chiral tetrahedral boranes with three B-C bonds and one B-N bond (BC 3 N), and examined the racemization process (Fig.…”
Section: Introductionmentioning
confidence: 99%